Forensic accounting litigation support and detection of public sector corruption in Nigeria - Akpootu, Eguono Juliet; Yusuf, Yahaya (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
Purpose: The rise in financial fraud cases in Nigeria's public sector, attributed to the ineffectiveness of statutory audits in detecting and preventing such activities, has led to an increased demand for forensic accountants. This study investigates the effect of forensic accounting in the detection of public sector corruption in Nigeria with a focus on three antigraft agencies.Methodology: The study adopted a descriptive survey research design and collected data using a structured questionnaire.  Using Taro Yamane's formula and a purposive sampling technique, four hundred and five (405) respondents of relevant staff of the antigraft agencies were selected for the study. The method of data analysis used was descriptive statistics and multiple linear regressions based on 386 questionnaires returned by the respondents.Results and conclusion: Findings of the study revealed that forensic accounting litigation support had a significant positive relationship with public sector corruption in Nigeria, indicating that the adoption of forensic accounting techniques is useful for detecting public sector corruption, and funds lost through bribery, embezzlement, accounting fraud, and financial malpractice can be recovered through the services of forensic accountants.Implication of findings: The study's findings suggest ways to enhance integrity, accountability, and financial governance in Nigeria, providing actionable insights for improved public sector practices and policies. The study recommends that special courts should be established to speed up the litigation process so that cases that are corruption-related in the Nigerian public sector do not linger for too long, as is the case in conventional courts.
Keywords: Anti-graft agencies; Embezzlement; Forensic accounting; Forensic accounting litigation support; Public sector corruption